Pengaruh Pola Asuh Orang Tua Terhadap Kecerdasan Emosional Anak Usia Dini di Nagari Batipuh Ateh - Mawardi; Pansla, Raiend Arasyi; Nikki Febrian, Muhammad; Viera, Angelina Diaz; Fahrul Gian, Rafsi; Azani, Aresto (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Parenting style is formed from their attitude towards their children and the emotional environment that underlies it. This study aims to examine the influence of parenting style on the emotional intelligence of early childhood. The method used in this study is a quantitative approach with a survey research design. The sample was selected using a simple random sampling technique, while data was collected through a Likert scale questionnaire distributed online. Data analysis was carried out using multiple linear regression techniques. The results of the study showed that the three parenting styles—authoritative, authoritarian, and permissive—simultaneously influenced children's emotional intelligence. Among the three parenting styles, authoritative parenting had the most significant positive impact. Thus, parenting styles have an important role in shaping children's emotional intelligence, so it is necessary to apply parenting styles that support their optimal development